2021
DOI: 10.1016/j.sjbs.2020.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of winter wheat varieties to tan spot in the North Caucasus region of Russia

Abstract: Tan spot caused by Pyrenophora tritici-repentis (Died.) Drechsler, in recent years, occupies an increasingly large area on the territory of Russia. Due to the wide distribution and economic significance of this disease, the search for resistant plants to the pathogen is relevant. This paper presents the results of a field assessment for 2017–2019 of 34 regionally distributed winter wheat varieties of Russian selection for resistance to P. tritici-repentis in the No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
0
11
0
2
Order By: Relevance
“…tritici Marchal, Pyrenophora tritici-repentis Died., Septoria tritici Rob. et Desm.,) [5][6][7]. For effective protection, it is important to understand the quantitative and qualitative composition of the spores of fungal pathogens (as an indicator of the presence of an aerogenic infection).…”
mentioning
confidence: 99%
“…tritici Marchal, Pyrenophora tritici-repentis Died., Septoria tritici Rob. et Desm.,) [5][6][7]. For effective protection, it is important to understand the quantitative and qualitative composition of the spores of fungal pathogens (as an indicator of the presence of an aerogenic infection).…”
mentioning
confidence: 99%
“…Disease severity was more important during growth season 2019-2020, compared to the following season because of the difference in humidity, air temperature and rainfall. These research results was demonstrated by Kremneva et al [22], which highlighted the effect of the higher average air temperatures and humidity on the susceptibility response of the most winter wheat varieties compared to drier years. These same weather factors have influenced the onset and development of the pathogen and the host susceptibility level to the disease in different studies of Fernandez et al [69].…”
Section: Discussionmentioning
confidence: 61%
“…This virulence variability was associated to eight races of Ptr [ 17 ]. The interaction of Ptr-wheat pathosystem follows in general an inverse of the gene-for-gene model [ 14 ] and race-specific [ 22 ]. The distinct races have the ability to produce three host selective toxins (HSTs) known as PtrToxA, PtrToxB, and PtrToxC, which are considered pathogenic factors.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, race 6 was found in Algeria and Morocco (Strelkov et al, 2002;Benslimane, 2018;Gamba et al, 2017), while races 7 and 8 were found only in the Middle East, Caucasus and Algeria, and Kazakhstan in 2018 and 2020 (Kokhmetova et al, 2020b;Benslimane, 2018, Ouaar et al, 2022. In 2021, in the North Caucasus region of Russia, races 1, 3 and 4 were identified (Kremneva et al, 2021). Races 2, 4, 5 and 7 were found in Tunisia by Kamel et al (2019).…”
Section: Discussionmentioning
confidence: 97%